Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1093/ije/dym004
|View full text |Cite
|
Sign up to set email alerts
|

Does social cohesion modify the association between area income deprivation and mental health? A multilevel analysis

Abstract: Income deprivation and social cohesion measured at community level are potentially important joint determinants of mental health. Further research on the impact of the social environment on mental health should investigate causal pathways in a longitudinal study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
186
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(217 citation statements)
references
References 50 publications
18
186
2
3
Order By: Relevance
“…It has been estimated that mental disorders account for 22.9% of all Years Lived with Disability (YLD) worldwide 3 , and for 32.4% of YLD if mental health problems that are not clinically diagnosable 4 are considered. Studies have established that, along with genetic and biological factors, social determinants influence individual and population mental health [5][6][7][8] , and that contextual factors, such as deprivation, poverty and violence negatively affect mental health. Analysing data from a study with twins, Caspi et al (2000) concluded that 20% of variance in children's behaviour problems were attributed to contextual factors, and that neighbourhood deprivation accounted for 5% of the contextual effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that mental disorders account for 22.9% of all Years Lived with Disability (YLD) worldwide 3 , and for 32.4% of YLD if mental health problems that are not clinically diagnosable 4 are considered. Studies have established that, along with genetic and biological factors, social determinants influence individual and population mental health [5][6][7][8] , and that contextual factors, such as deprivation, poverty and violence negatively affect mental health. Analysing data from a study with twins, Caspi et al (2000) concluded that 20% of variance in children's behaviour problems were attributed to contextual factors, and that neighbourhood deprivation accounted for 5% of the contextual effect.…”
Section: Introductionmentioning
confidence: 99%
“…The psychosocial pathway relies on status competition and insecurity 12 , leading to social problems 13 , such as lack of social cohesion and violence, low levels of trust and weaker community life 12 . Evidence shows that these psychosocial factors can affect health through physiological effects of chronic stress and through their effects on health-related behaviours and individuals' self-esteem 14 Those, in turn, are known to cause psychosocial stress 5,6 and to increase the risk of developing mental health problems at an individual level [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested that income assessed on a contextual level is directly related to the concepts of social capital and cohesion, which include the ways in which society is organized, through the establishment of norms of reciprocity and trust that help the formation of social ties and determine health at the individual level 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…FONE et al, 2007;JAYASINGHE et al, 2009 Os autores também não encontraram associação estatisticamente significante entre a ocupação e o componente físico e mental da escala SF-36. Para os mesmos autores, considerando os 1.063 indivíduos com idade maior ou igual a 35 anos, a proporção que nunca havia dosado o colesterol sanguíneo reduziu-se para 38% e a taxa de hipercolesterolemia autorreferida aumentou para 18%.…”
Section: Análise Multivariadaunclassified